Pemberdayaan Kader Posyandu dalam Pemilihan Kontrasepsi yang sesuai dengan Status Gizi - Ilmiya, Istifadatul (Dental Agromedis, 2025)
Lack of community participation in family planning programs with the use of contraception can cause health problems for mothers and children, and affect social conditions and the level of family welfare. Empowerment of cadres in promotion and counseling about various methods of family planning and being able to determine nutritional status is considered important for the success of the family planning program. The purpose of this service is to increase the knowledge and skills of cadres related to contraceptives and determine the nutritional status of women of childbearing age. The results of the service showed that there was a significant increase in cadre knowledge after education related to various contraceptives was carried out and there was an increase in ability related to determining nutritional status in women of childbearing age. The conclusion of community service activities in this case is that education and simulation methods can increase cadre knowledge regarding contraception and cadre skills in determining nutritional status in women of childbearing age.Keywords: Cadre empowerment, Contraception, Nutritional Status